PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN NON PERFORMING LOAN (NPL) TERHADAP PROFITABILITAS (ROA) PADA PT. BANK NEGARA INDONESIA (PERSERO) TBK - Setiawan, Arif; Puji Muniarty (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR) and Non-Performing Loan (NPL) on profitability as measured by Return on Assets (ROA) at PT Bank Negara Indonesia (Persero) Tbk. The research method used is a quantitative approach with an associative design. The data utilized are secondary data in the form of annual financial statements of PT Bank Negara Indonesia (Persero) Tbk during the observation period. The data analysis techniques include multiple linear regression analysis, classical assumption tests, and hypothesis testing consisting of t-test and F-test. The results show that partially, the Capital Adequacy Ratio (CAR) has a positive and significant effect on Return on Assets (ROA), while Non-Performing Loan (NPL) has a negative and significant effect on Return on Assets (ROA). Simultaneously, CAR and NPL have a significant effect on ROA. These findings indicate that higher capital adequacy and lower levels of non-performing loans will improve the bank’s profitability.In conclusion, capital management and credit risk control are crucial factors in enhancing the financial performance of banks. Therefore, PT Bank Negara Indonesia (Persero) Tbk is expected to maintain an optimal CAR level and reduce NPL ratios to improve profitability.